2019
DOI: 10.1038/s41545-019-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water vulnerability in less-populated communities in Texas to wastewater-derived contaminants

Abstract: De facto potable reuse occurs when treated wastewater is discharged upstream of drinking water treatment plants (DWTPs) and can lead to contaminants of emerging concern (CECs) occurring in potable water. Our prior research, focusing on larger communities that each serve >10,000 people across the USA, indicates that elevated de facto reuse (DFR) occurs in Texas, and thus we added to our model DWTPs serving smaller communities to understand their vulnerability to CECs. Here, we show that twothirds of all surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…There is nearly 4× higher bromide ion and up to 30× higher iodine concentrations in treated wastewater than untreated drinking waters. Therefore, the occurrence of Br and I species in wastewater effluents can have implications for downstream source waters; unplanned or indirect wastewater reuse frequently occurs with dilution factors less than 10-fold. Our analysis suggests drinking water sources impacted by upstream wastewater discharges would benefit from monitoring for Br – plus individual inorganic species and total iodine to comprehensively assess the risk of forming I-DBPs.…”
Section: Resultsmentioning
confidence: 97%
“…There is nearly 4× higher bromide ion and up to 30× higher iodine concentrations in treated wastewater than untreated drinking waters. Therefore, the occurrence of Br and I species in wastewater effluents can have implications for downstream source waters; unplanned or indirect wastewater reuse frequently occurs with dilution factors less than 10-fold. Our analysis suggests drinking water sources impacted by upstream wastewater discharges would benefit from monitoring for Br – plus individual inorganic species and total iodine to comprehensively assess the risk of forming I-DBPs.…”
Section: Resultsmentioning
confidence: 97%
“…De facto reuse based on average streamflow has been estimated as at least 1% for approximately 50% of U.S. drinking water treatment plant (DWTP) intakes (i.e., 1% was the median contribution of wastewater flow to U.S. DWTPs and provides a realistic reference point that would be applicable to a broad range of such plants). Others have examined the impacts of de facto reuse on small communities (Nguyen & Westerhoff 2019) and found that DWTPs serving them have higher levels of de facto reuse.…”
Section: Introductionmentioning
confidence: 99%
“…De facto reuse based on the proportion of wastewater in any stream varies with time, as wastewater discharge flows and streamflow vary (Merritt 1983;Corbitt 1999;Fernandez et al 2008;Daelman et al 2015). Municipal wastewater discharge flows are generally considered directly related to the number of people served by a wastewater treatment plant (WWTP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular attention should be paid to compounds that are scarcely biodegradable, such as pharmaceuticals, personal care products, hormones, food additives, artificial sweeteners, pesticides, and dyes among others [4][5][6]. Due to their distinct chemical properties (polarity, functional groups, solubility,…) and potential persistence, CECs are poorly removed by conventional wastewater treatment methodologies and are thus frequently detected in the wastewater treatment plant (WWTP) effluents [7]. These effluents act as a constant low-level source of such substances to the environment.…”
Section: Introductionmentioning
confidence: 99%